The importance of playful activities in the motor and social development of children who practice sports (Research, Society and Development, 2026)
Child development is a process that involves motor, cognitive, emotional, and social dimensions, occurring in an integrated way throughout childhood. The general objective of the present study was to analyze the contribution of playful activities to the motor and social development of children who practice sports, and the specific objectives were: to identify the motor skills stimulated through recreational activities; to verify how playful practices contribute to socialization and teamwork; to describe the experiences lived during the supervised internship; and to analyze the importance of play as a pedagogical strategy in Physical Education. A qualitative, descriptive study of the experience-report type was conducted, supported by a narrative review. Based on the experience during the application of the proposed activities, it was observed that the practices developed contributed to the improvement of participants' motor skills, especially regarding motor coordination, balance, and body control. Conducting this study made it possible to understand, in practice, the importance of playful activities in the development of children inserted in the sports context. During the internship, it became evident that play, when well directed, contributes significantly to both motor and social development.